If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x) = 3(2x + y) Remove parenthesis around (2x) 2 * 2x = 3(2x + y) Multiply 2 * 2 4x = 3(2x + y) 4x = (2x * 3 + y * 3) 4x = (6x + 3y) Solving 4x = 6x + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4x + -6x = 6x + -6x + 3y Combine like terms: 4x + -6x = -2x -2x = 6x + -6x + 3y Combine like terms: 6x + -6x = 0 -2x = 0 + 3y -2x = 3y Divide each side by '-2'. x = -1.5y Simplifying x = -1.5y
| x+0.07x=25.68 | | 0.003x-.2=0.01 | | V-9.12=7.55 | | 0.0196=m^2 | | -3y=20 | | x-6.34=35.1 | | -8x-9=9x+42 | | (u-8)(u-4)= | | 9+2(5m-3)= | | 3(x-1)=x+3 | | 2n+1=-31 | | 15y^2+25y+10=0 | | 2x+3(x+4)=12 | | -6k+8=-5k | | r^3-3r^2+2=0 | | G(x)=2x^2-6x-18 | | 4x^3+6x^2-18x+18=0 | | (-12x+6)+(x-15)= | | .94(x-2)=.02(6x-3)-.02 | | 0=-157+0.05v^2 | | -4(4p+2)-12=3(2p+8) | | x+50+3x=90 | | 3(c-1)+8=14 | | 5x-55=35 | | (9x+12)-(2x+8)= | | -11r=4r+55 | | -7x(t+4)=0 | | 8t+6t-t= | | 9-1/4n=15 | | y+2=4y+1 | | 113.0=3.14r^2 | | n=-8n-7n |